Understanding Consumer Perceptions Of Pinedrama Through Sentiment Analysis Of Google Play Store Reviews - Chairunnisaa M Z Huzaen (Journal of Studies in Academic, Humanities, Research, and Innovation, 2026)
The rapid growth of digital entertainment platforms has increased consumer interest in mobile applications that provide short-drama content. PineDrama is one of the emerging digital entertainment applications that offers short-form video content combined with reward-based engagement features. This study aims to explore consumer perceptions toward PineDrama through online reviews collected from the Google Play Store. A quantitative descriptive approach was employed using sentiment analysis and keyword exploration methods. The study utilized a large-scale dataset consisting of 40,059 user reviews collected through a web scraping process, providing comprehensive insights into consumer perceptions toward the application. Data preprocessing included text cleaning and normalization to improve textual quality before analysis. Sentiment classification was conducted using a rating-based labeling approach, where ratings of 4–5 stars were categorized as positive, 3-star ratings as neutral, and ratings of 1–2 stars as negative. The findings revealed that positive sentiment dominated the dataset, accounting for 84.49% of reviews, followed by negative sentiment (12.22%) and neutral sentiment (3.29%). Positive reviews were primarily associated with entertainment value, drama content, and reward opportunities, while negative reviews mainly concerned login difficulties, account accessibility, and application performance issues. Furthermore, user satisfaction, content consumption, and reward mechanisms emerged as the most frequently discussed topics in user reviews. These findings indicate that the combination of engaging content and attractive reward features plays an important role in shaping positive consumer perceptions and encouraging continued user engagement. The study contributes practical insights for digital entertainment platform management by highlighting the importance of maintaining content quality, optimizing reward mechanisms, improving system reliability, and enhancing account accessibility. However, the findings should be interpreted with caution because the rating-based sentiment classification approach may not always fully reflect the sentiment expressed in review texts. Despite this limitation, the study provides valuable insights into consumer perceptions and user experiences within digital entertainment platforms.